Solid waste management of the city of Juliaca (Puno, Peru) - Huamaní Montesinos, Candelaria (2020)
The city of Juliaca has serious problems of municipal solid waste management, which in recent years has led to adverse implications of governance, social conflicts and the health of the population. The objective was to characterize the solid waste management factors and conditions, evaluating the possibility of reuse and determining the costs and revenues generated by the activity. Information was collected, by means of a questionnaire of surveys in a random way and by coexistence to a sample of 267 heads of family in six zones of greater population concentration, which were processed by means of descriptive statistics supplemented with the secondary information to determine the capacity of generation of urban waste contrasted with projections for 10 years. The results, referring to the generation, classification and sale of compost and inputs of inorganic waste induced positive profitability for the year 2017, as a result of the generation of 75,000 tons per year of municipal solid waste; of which 72% were usable and 28% were not. It is concluded that the transformation of organic solid waste from paper-cardboard, plastics, metal glass including the production of compost can contribute to sustainability, improve the equitable income of the benefits resulting from the responsible use of municipal resources.